Reformulasi Pembelajaran Sejarah: Sebuah Tantangan - Sardiman Sardiman (ISTORIA: Jurnal Pendidikan dan Sejarah, 2017)
AbstractHistory is a strategic subject and very important to form a private student who love the homeland or spirited patriotism. Learning history in schools has started from the elementary school unit up to high school level. Of course, with material whose capacity follows the development of students. However, learning history in schools is considered less attractive, resulting in students feel bored and tired. It makes the outcome of learning history not optimal. Many critics say historical learning tends to be rote. Therefore, creative and innovative learning methods are needed to teach history to the students. This study aims to reformulate the inspiring and inspiring learning history. In addition, the need to explore the meaning of learning history that can be reflected with everyday life. This research is a qualitative research through several stages of research, including observation, in-depth interviews, and documentary. The results show that in history learning needs to be emphasized on the search for the meaning of a historical event associated with the values of life. History has a reflective, anti-inspirational function in anti, historical learning can build wisdom in the life of society and nation, histories make man wise. Reformulating one's learning history is done through renewal in historical learning activities to be more fun and inspirational.  Keywords: reformulate, learning history, students